A method for preparing lithium iron manganese phosphate positive electrode material based on titanium dioxide by-product ferrous sulfate
By hydrolyzing the impurities and oxidation co-precipitation of titanium dioxide by-product ferrous sulfate, the problem of utilization of impurities in the by-product ferrous sulfate in titanium dioxide production is solved, and the preparation of high-performance lithium manganese iron phosphate positive electrode material is realized, which is promoted. The sustainable development of titanium dioxide production enterprises.
Patent Information
- Application Number
- CN202310841061.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-10
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-07-10
AI Technical Summary
The by-product produced in the titanium dioxide production process, ferrous sulfate heptahydrate contains impurities such as titanium, magnesium, aluminum, etc., which is difficult to directly utilize, making it difficult to produce battery-grade lithium manganese phosphate, affecting the sustainable development of titanium dioxide production enterprises.
By hydrolyzing the titanium dioxide by-product ferrous sulfate, adjusting the pH range, removing impurities such as titanium, magnesium, aluminum, etc., retaining manganese impurities, and then replenishing manganese and oxidation and co-precipitation to obtain high stability and good electrochemical properties. Lithium manganese iron phosphate positive electrode material.
The production of battery-grade lithium manganese ferrous sulfate materials is achieved by using titanium dioxide by-product ferrous sulfate, which has high safety, stability and high energy density, reduces production costs and promotes the sustainable development of titanium dioxide production enterprises.
Smart Images

Figure CN116902951B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery positive electrode materials, and specifically relates to a method for preparing lithium iron manganese phosphate positive electrode material based on ferrous sulfate produced as a byproduct of titanium dioxide. Background Art
[0002] A large amount of ferrous sulfate heptahydrate byproduct is produced during the production of titanium dioxide. Using ferrous sulfate, a byproduct of titanium dioxide, as an iron source to synthesize iron phosphate and lithium iron phosphate positive electrode materials can not only reduce the synthesis cost of lithium iron phosphate, but also has important significance for solving the recycling of ferrous sulfate, a waste byproduct of titanium dioxide production, and can achieve sustainable development of titanium dioxide production enterprises.
[0003] Among the positive electrode materials of lithium-ion batteries, LiFePO4 (LFP) has the advantages of high safety and good cycle performance. It is currently mainly used in energy storage, power battery, new energy vehicle, etc. However, it also has the disadvantages of low energy density and poor low temperature performance. 2+ / 3+ The redox potential of Fe is higher than that of Fe 2+ / 3+ (3.4V), when Mn partially replaces Fe in LFP, the resulting LiMn x Fe 1-x PO4(LMFP) material has higher energy density than LFP. At the same time, due to the strong covalent PO4 3- In addition, in LMFP material, Mn and Fe are substituted at the atomic level, so LMFP has similar tap density and good chemical stability to LFP.
[0004] However, the titanium dioxide byproduct ferrous sulfate contains a variety of impurities such as titanium, manganese, and aluminum, making it difficult to directly use and produce lithium iron manganese phosphate. Therefore, making full and comprehensive use of titanium dioxide byproduct ferrous sulfate to produce battery-grade lithium iron manganese phosphate and achieve sustainable development of titanium dioxide production enterprises is a technical problem that needs to be solved urgently. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing lithium iron manganese phosphate positive electrode material based on titanium dioxide by-product ferrous sulfate. By simply hydrolyzing and removing the titanium dioxide by-product ferrous sulfate, the purpose of using titanium dioxide by-product ferrous sulfate to prepare battery-grade lithium iron manganese phosphate material is achieved. The obtained material is a lithium iron manganese phosphate positive electrode material with high safety and stability and high energy density.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a lithium manganese iron phosphate positive electrode material, comprising the following steps:
[0008] S1. Prepare a solution of ferrous sulfate produced as a byproduct of titanium dioxide, adjust the pH, stir, and then add manganese salt to obtain a solution containing Mn 2+ of ferrous sulfate solution;
[0009] S2, to the Mn-containing 2+ Adding an oxidant and a phosphorus source to a ferrous sulfate solution, adjusting the pH, stirring, filtering, and washing to obtain manganese-doped basic iron phosphate;
[0010] S3, dissolving the basic ferric phosphate, neutralizing it with acid, filtering, washing, and drying to obtain manganese-doped ferric phosphate hydrate;
[0011] S4, aerobically calcining the ferric phosphate hydrate to obtain manganese-doped anhydrous ferric phosphate;
[0012] S5, mixing the anhydrous ferric phosphate, a lithium source and a reducing sugar, ball milling, and drying to obtain a mixture;
[0013] S6. calcining the mixture in the absence of oxygen to obtain the lithium manganese iron phosphate positive electrode material.
[0014] In step S1, the titanium dioxide by-product ferrous sulfate refers to ferrous sulfate heptahydrate, a by-product produced in the titanium dioxide production process.
[0015] The impurities and their contents in the titanium dioxide by-product ferrous sulfate are: titanium 1000-2000 ppm, manganese 800-900 ppm, and magnesium 1800-2000 ppm.
[0016] In step S1, the pH is 4.5 to 6.5, preferably 5 to 6. The pH is adjusted by ammonia water.
[0017] In step S1, the stirring conditions are: temperature of 60-80°C, preferably 80°C, time of 1-5h, preferably 3h, and stirring speed of 250-450rpm, preferably 350rpm.
[0018] In step S1, the manganese salt is manganese sulfate and / or manganese acetate.
[0019] The amount of the manganese salt used is 1 to 80 mol%, preferably 40 to 50 mol%, of the ferrous sulfate.
[0020] The Mn-containing 2+ The molar ratio of manganese to iron in the ferrous sulfate solution is (0.67~1):1, such as 0.67:1, 0.82:1, and 1:1.
[0021] In step S2, the oxidant is one or more of hydrogen peroxide, oxygen and sodium chlorate.
[0022] The molar ratio of the oxidant to the ferrous sulfate is (0.45-0.55):1, preferably 0.5:1.
[0023] The feed rate of the oxidant is 0.1-0.5 ml / min, preferably 0.2 ml / min.
[0024] In step S2, the phosphorus source is one or more of ammonium phosphate, diammonium hydrogen phosphate, diammonium phosphate and phosphoric acid. The molar ratio of phosphorus to iron in the basic ferric phosphate is 1:(1.01-1.05), preferably 1:1.
[0025] The feeding rate of the phosphorus source is 3-5 ml / min, preferably 4 ml / min.
[0026] In step S2, the pH is 7 to 10, preferably 7 to 9. The pH is adjusted by ammonia water.
[0027] In step S2, the stirring conditions are: time is 1 to 3 hours, preferably 2 hours, and the stirring speed is 350 to 750 rpm, preferably 350 rpm.
[0028] In step S3, the acid is one or more of phosphoric acid, sulfuric acid, oxalic acid and hydrochloric acid.
[0029] In step S3, the drying conditions are: temperature of 50-80°C, preferably 80°C, and time of 6-12h, preferably 10h.
[0030] In step S4, the conditions for aerobic calcination are: temperature of 500-700° C., preferably 550-600° C., and time of 3-6 hours, preferably 4-5 hours.
[0031] In step S5, the lithium source is one or more of lithium carbonate, lithium hydroxide and lithium acetate.
[0032] The lithium source Li + With the anhydrous iron phosphate PO4 3- The molar ratio is (1.01-1.05):1, preferably 1.05:1.
[0033] In step S5, the reducing sugar is one or more of glucose, fructose and galactose.
[0034] Based on the lithium manganese iron phosphate positive electrode material, the amount of reducing sugar is 10% to 20%, preferably 15%.
[0035] In step S5, the ball milling conditions are: carried out in a planetary ball mill, the ball milling speed is 300-600 rpm / min, preferably 500 rpm / min, and the ball milling time is 4-8 h, preferably 5 h.
[0036] In step S5, the drying conditions are: temperature of 50-80°C, preferably 80°C, and time of 3-6h, preferably 4h.
[0037] In step S6, the conditions for oxygen-free calcination are: under an inert atmosphere, a temperature of 650 to 850° C., preferably 700 to 750° C., and a time of 8 to 12 hours, preferably 10 hours.
[0038] The inert gas is nitrogen or argon.
[0039] In step S6, the chemical formula of the lithium manganese iron phosphate positive electrode material is LiMn x Fe 1-x PO4, where x is between 0.4 and 0.5, such as 0.4, 0.45, and 0.5.
[0040] In step S6, the particle size of the lithium manganese iron phosphate positive electrode material is 1 to 15 μm, preferably 3 μm.
[0041] The beneficial effects achieved by the present invention are as follows:
[0042] 1. The present invention can adjust the pH range so that the ferrous sulfate produced as a byproduct of titanium dioxide can remove impurities such as titanium, magnesium, and aluminum during the hot dissolution process while retaining manganese impurities. This not only simplifies the process, but also reduces the amount of manganese supplementation and reduces costs.
[0043] 2. The present invention obtains a basic iron phosphate precursor by manganese supplementation and simple oxidation coprecipitation, and then obtains a lithium iron manganese phosphate positive electrode material with high stability and good electrochemical properties, thereby achieving the purpose of preparing battery-grade lithium iron manganese phosphate material from ferrous sulfate, a byproduct of titanium dioxide.
[0044] 3. The method provided by the present invention is simple to operate, has a short process, is widely used, and has high economic benefits. It is of great significance for solving the problem of recycling the waste by-product ferrous sulfate in the current titanium dioxide production, and can achieve the sustainable development of titanium dioxide production enterprises. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a process flow chart for preparing lithium manganese iron phosphate positive electrode material in Example 1.
[0046] Figure 2 LiMn prepared in Example 3 0.5 Fe 0.5 XRD of PO4.
[0047] Figure 3 LiMn prepared in Example 2 0.45 Fe 0.55 SEM image of PO4.
[0048] Figure 4 LiMn prepared in Example 1 0.4 Fe 0.6 The charge and discharge curve of PO4. DETAILED DESCRIPTION
[0049] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.
[0050] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0051] Unless otherwise specified, the reagents, biological materials, instruments, etc. used in the following examples can be obtained from commercial sources.
[0052] The electrochemical performance tests in the following examples are as follows:
[0053] Preparation of CR2032 button battery: The prepared LiMn x Fe 1-x PO4, as the positive electrode material of lithium-ion battery, was uniformly mixed with acetylene black and polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, stirred for 12 hours, and then coated into electrode sheets by a coating machine. The electrode sheets were placed in a vacuum drying oven and dried at 80°C for 12 hours, and then punched into positive electrode sheets with a diameter of 12 mm. 1 mol / L LiPF6 was used as the electrolyte, polyethylene film (PE) was used as the diaphragm, and metal lithium sheet was used as the reference electrode. The material was made into CR2032 button batteries in a glove box filled with argon.
[0054] Electrochemical performance test: At 25°C, the button cell was tested for constant current charge and discharge using the Land-CT2001A battery test system from Wuhan Landian Company. The test voltage range was 2.5 to 3.7V.
[0055] Example 1
[0056] A method for preparing lithium iron manganese phosphate positive electrode material based on titanium dioxide by-product ferrous sulfate, such as Figure 1 As shown, the following steps are included:
[0057] (1) Hot-dissolving impurities: 16.6806 g of ferrous sulfate produced as a byproduct of titanium dioxide was heated and dissolved to prepare a 0.5 mol / L solution, which was then placed in a 1000 ml four-necked flask and heated and stirred in a constant temperature water bath at 80°C. The stirring speed was kept constant at 350 rpm, and NH3·H2O was added to adjust the pH. The pH value was measured by a pH meter and the pH range was controlled to be 5 to 6. The reaction was continued for 3 h. After the reaction was completed, 9.8036 g of manganese acetate tetrahydrate was added to supplement manganese to obtain a Mn-containing flask. 2+ of ferrous sulfate solution.
[0058] (2) Coprecipitation: Add the Mn-containing 2+ 3.060 ml of 30% H2O2 and 14.9060 g of ammonium phosphate (prepared into a 0.5 mol / L solution) were added to the ferrous sulfate solution, and a peristaltic pump was used for stirring. NH3·H2O was added to control the pH to be maintained at about 7.0. The mixture was reacted for 2 h, filtered, washed, and dried to obtain manganese-doped basic iron phosphate (precursor 1).
[0059] (3) Acid neutralization: dissolve the manganese-doped basic ferric phosphate obtained in step (2), add 5 ml of 85% phosphoric acid for neutralization, maintain magnetic stirring, and after the reaction is completed, filter and wash, and dry in a blower dryer at 80° C. for 10 h to obtain manganese-doped ferric phosphate hydrate (precursor 2).
[0060] (4) Aerobic calcination: The manganese-doped ferric phosphate hydrate obtained in step (3) is fully ground and placed in a muffle furnace for aerobic calcination to burn off excess impurities. The calcination temperature is 550° C. and the calcination time is 4 h to obtain manganese-doped anhydrous ferric phosphate, which is fully ground and collected for later use.
[0061] (5) Ball milling: 7.55 g of the manganese-doped anhydrous ferric phosphate obtained in step (4) was mixed with 1.212 g of lithium hydroxide and 0.79 g of glucose, and an appropriate amount of ethanol was added for ball milling. After the ball milling was completed, the sample was placed in a blower dryer at 80° C. for 4 h to obtain a mixed sample, which was then ground and collected.
[0062] (6) Oxygen-free calcination: The mixed sample obtained in step (5) was placed in a nitrogen atmosphere for heat treatment at a temperature of 700° C. for 10 h to obtain LiMn 0.4 Fe 0.6 PO4. The manganese to iron ratio is 0.67.
[0063] Example 2
[0064] A method for preparing lithium iron manganese phosphate positive electrode material based on ferrous sulfate produced as a byproduct of titanium dioxide, specifically comprising the following steps:
[0065] (1) 15.2906 g of ferrous sulfate produced as a byproduct of titanium dioxide was heated and dissolved to prepare a 0.5 mol / L solution, and then placed in a 1000 ml four-necked flask, heated and stirred in a constant temperature water bath at 80° C., and the stirring speed was kept constant at 350 rpm. NH 3·H 2 O was added to adjust the pH value, and the pH value was measured by a pH meter, and the pH range was controlled to be 5 to 6. The reaction was carried out for 3 h. After the reaction was completed, 11.0291 g of manganese acetate tetrahydrate was added to supplement manganese to obtain a Mn-containing solution. 2+ of ferrous sulfate solution.
[0066] (2) Add the Mn-containing 2+2.809 ml of 30% H2O2 and 14.9060 g of ammonium phosphate (prepared into a 0.5 mol / L solution) were added to the ferrous sulfate solution, and a peristaltic pump was used to stir and NH3·H2O was added to control the pH to be maintained at about 7.5. The mixture was reacted for 2 h, filtered, washed, and dried to obtain manganese-doped basic iron phosphate.
[0067] (3) dissolving the manganese-doped basic iron phosphate obtained in step (2), adding 5 ml of 85% phosphoric acid for neutralization, maintaining magnetic stirring, and after the reaction is completed, filtering and washing, and drying in a blower dryer at 80° C. for 10 h to obtain manganese-doped iron phosphate hydrate.
[0068] (4) The manganese-doped ferric phosphate hydrate obtained in step (3) is fully ground and placed in a muffle furnace for aerobic calcination to burn off excess impurities. The calcination temperature is 550° C. and the calcination time is 4 h to obtain manganese-doped anhydrous ferric phosphate, which is fully ground and collected for later use.
[0069] (5) Take 7.55 g of the manganese-doped anhydrous ferric phosphate obtained in step (4), mix it with 1.224 g of lithium hydroxide and 0.948 g of glucose, add an appropriate amount of ethanol and ball mill. After the ball milling is completed, place the sample in a forced air dryer at 80° C. for 4 h to dry, grind it, and collect it.
[0070] (6) The mixed sample obtained in step (5) was placed in a nitrogen atmosphere for heat treatment at a calcination temperature of 700° C. for 10 h to obtain LiMn 0.45 Fe 0.55 PO4. The manganese to iron ratio is 0.82.
[0071] Example 3
[0072] A method for preparing lithium iron manganese phosphate positive electrode material based on ferrous sulfate produced as a byproduct of titanium dioxide, specifically comprising the following steps:
[0073] (1) 13.9005 g of ferrous sulfate produced as a byproduct of titanium dioxide was heated and dissolved to prepare a 0.5 mol / L solution, which was then placed in a 1000 ml four-necked flask and heated and stirred in a constant temperature water bath at 80° C. The stirring speed was kept constant at 350 rpm, and NH 3 ·H 2 O was added to adjust the pH. The pH value was measured by a pH meter and the pH range was controlled to be 5 to 6. The reaction was continued for 3 h. After the reaction was completed, 12.2545 g of manganese acetate tetrahydrate was added to supplement manganese.
[0074] (2) Add the Mn-containing 2+ 2.554 ml of 30% H2O2 and 14.906 g of ammonium phosphate (prepared into a 0.5 mol / L solution) were added to the ferrous sulfate solution, and a peristaltic pump was used to stir and NH3·H2O was added to control the pH to be maintained at about 8.0. The mixture was reacted for 2 h, filtered, washed, and dried to obtain manganese-doped basic iron phosphate.
[0075] (3) dissolving the manganese-doped basic iron phosphate obtained in step (2), adding 5 ml of 85% phosphoric acid for neutralization, maintaining magnetic stirring, and after the reaction is completed, filtering and washing, and drying in a blower dryer at 80° C. for 10 h to obtain manganese-doped iron phosphate hydrate.
[0076] (4) The manganese-doped ferric phosphate hydrate obtained in step (3) is fully ground and placed in a muffle furnace for aerobic calcination to burn off excess impurities. The calcination temperature is 550° C. and the calcination time is 4 h to obtain manganese-doped anhydrous ferric phosphate, which is fully ground and collected for later use.
[0077] (5) Take 7.55 g of the manganese-doped anhydrous ferric phosphate obtained in step (4), mix it with 1.236 g of lithium hydroxide and 1.106 g of glucose, add an appropriate amount of ethanol and ball mill. After the ball milling is completed, place the sample in a forced air dryer at 80° C. for 4 h to dry, grind it, and collect it.
[0078] (6) The mixed sample obtained in step (5) was placed in a nitrogen atmosphere for heat treatment at a calcination temperature of 700° C. for 10 h to obtain LiMn 0.5 Fe 0.5 PO4. The manganese to iron ratio is 1.
[0079] Comparative Example 1
[0080] A method for preparing lithium iron manganese phosphate positive electrode material based on ferrous sulfate produced as a byproduct of titanium dioxide, specifically comprising the following steps:
[0081] (1) Hot-dissolving impurities: 25.0209 g of ferrous sulfate, a by-product of titanium dioxide, was heated and dissolved to prepare a 0.5 mol / L solution, which was then placed in a 1000 ml four-necked flask and heated and stirred in a constant temperature water bath at 80°C. The stirring speed was kept constant at 350 rpm, and NH3·H2O was added to adjust the pH. The pH value was measured by a pH meter and the pH range was controlled to be 5 to 6. The reaction was continued for 3 h. After the reaction was completed, 2.4509 g of manganese acetate was added to supplement manganese to obtain a Mn-containing flask. 2+ of ferrous sulfate solution.
[0082] (2) Add the Mn-containing 2+ To the ferrous sulfate solution, 4.597 ml of 30% H2O2 and 14.906 g of ammonium phosphate (configured into a 0.5 mol / L solution) were added, and a peristaltic pump was used for stirring. NH3·H2O was added to control the pH to be maintained at about 8.5. The mixture was reacted for 2 h, filtered, washed, and dried to obtain manganese-doped basic iron phosphate.
[0083] (3) dissolving the manganese-doped basic iron phosphate obtained in step (2), adding 5 ml of 85% phosphoric acid for neutralization, maintaining magnetic stirring, and after the reaction is completed, filtering and washing, and drying in a blower dryer at 80° C. for 10 h to obtain manganese-doped iron phosphate hydrate.
[0084] (4) The manganese-doped ferric phosphate hydrate obtained in step (3) is fully ground and placed in a muffle furnace for aerobic calcination to burn off excess impurities. The calcination temperature is 550° C. and the calcination time is 4 h to obtain manganese-doped anhydrous ferric phosphate, which is fully ground and collected for later use.
[0085] (5) Take 7.55 g of the manganese-doped anhydrous ferric phosphate obtained in step (4), mix it with 1.248 g of lithium hydroxide and 1.264 g of glucose, add an appropriate amount of ethanol and ball mill. After the ball milling is completed, place the sample in a forced air dryer at 80° C. for 4 h to dry, grind it, and collect it.
[0086] (6) The mixed sample obtained in step (5) was placed in a nitrogen atmosphere for heat treatment at a calcination temperature of 700° C. for 10 h to obtain LiMn 0.1 Fe 0.9 PO4. The manganese to iron ratio is 0.1.
[0087] Comparative Example 2
[0088] A method for preparing lithium iron manganese phosphate positive electrode material based on ferrous sulfate produced as a byproduct of titanium dioxide, specifically comprising the following steps:
[0089] (1) 22.2408 g of ferrous sulfate produced as a byproduct of titanium dioxide was heated and dissolved to prepare a 0.5 mol / L solution, which was then placed in a 1000 ml four-necked flask and heated and stirred in a constant temperature water bath at 80°C. The stirring speed was kept constant at 350 rpm, and NH3·H2O was added to adjust the pH. The pH value was measured by a pH meter and the pH range was controlled to be 5 to 6. The reaction was continued for 3 h. After the reaction was completed, 4.9018 g of manganese acetate tetrahydrate was added to supplement manganese.
[0090] (2) Add the Mn-containing 2+ To the ferrous sulfate solution, 4.086 ml of 30% H2O2 and 14.906 g of ammonium phosphate (configured into a 0.5 mol / L solution) were added, and a peristaltic pump was used for stirring. NH3·H2O was added to control the pH to be maintained at about 9.0. The mixture was reacted for 2 h, filtered, washed, and dried to obtain manganese-doped basic iron phosphate.
[0091] (3) dissolving the manganese-doped basic iron phosphate obtained in step (2), adding 5 ml of 85% phosphoric acid for neutralization, maintaining magnetic stirring, and after the reaction is completed, filtering and washing, and drying in a blower dryer at 80° C. for 10 h to obtain manganese-doped iron phosphate hydrate.
[0092] (4) The manganese-doped ferric phosphate hydrate obtained in step (3) is fully ground and placed in a muffle furnace for aerobic calcination to burn off excess impurities. The calcination temperature is 550° C. and the calcination time is 4 h to obtain manganese-doped anhydrous ferric phosphate, which is fully ground and collected for later use.
[0093] (5) Take 7.55 g of the manganese-doped anhydrous ferric phosphate obtained in step (4), mix it with 1.260 g of lithium hydroxide and 1.422 g of glucose, add an appropriate amount of ethanol and ball mill. After the ball milling is completed, place the sample in a forced air dryer at 80° C. for 4 h to dry, grind it, and collect it.
[0094] (6) The mixed sample obtained in step (5) was placed in a nitrogen atmosphere for heat treatment at a calcination temperature of 700° C. for 10 h to obtain LiMn 0.2 Fe 0.8 PO4. The manganese to iron ratio is 0.25.
[0095] Effect verification:
[0096] 1. Figure 2 LiMn prepared in Example 3 0.5 Fe 0.5 XRD of PO4. Through XRD characterization, the product obtained in Example 3 is consistent with the PDF card 04-010-3115 of LiFePO4, which is an olivine structure with a space group of Pmnb. This shows that the method for preparing lithium manganese iron phosphate positive electrode material based on titanium dioxide byproduct ferrous sulfate described in the present invention is feasible. The XRD patterns of the materials obtained in Examples 1 and 2 are basically consistent with those in Example 3.
[0097] 2. Figure 3 This is the SEM image of the material obtained in Example 2, which has an irregular spherical structure and a particle size of about 3 μm.
[0098] 3. Figure 4 The first cycle charge-discharge curve of the material obtained in Example 1 at 0.1C and 25°C. The first cycle discharge capacity can reach 161.2 mAh·g -1 , which has significantly improved specific capacity compared to traditional lithium iron phosphate positive electrode materials.
[0099] 4. The comparison table of impurity contents of the titanium dioxide byproduct ferrous sulfate before and after the impurity removal in step S1 is as follows:
[0100] Table 1 Comparison of impurity content before and after impurity removal in step S1
[0101]
[0102] From the comparison results in Table 1, it can be seen that by controlling the pH during the hot dissolution process of ferrous sulfate produced as a by-product of titanium dioxide, titanium and magnesium impurities can be effectively removed while manganese impurities can be retained. This not only simplifies the process, but also reduces the amount of manganese supplementation and reduces costs.
[0103] 5. The comparison results of the performance of lithium manganese iron phosphate of the above examples 1-3 and comparative examples 1 and 2 are as follows:
[0104] Table 2 Performance comparison of lithium manganese iron phosphate prepared in each embodiment and comparative example
[0105]
[0106] It can be seen from Table 2 that the tap density of the materials obtained in Examples 1-3 is greater than the national standard for lithium iron phosphate, the first-cycle discharge specific capacity at 0.1C and 25°C is higher than that of the materials obtained in Comparative Examples 1-2, the capacity retention rate is better, and the capacity retention rate is high after 500 cycles at 0.1C and 45°C, indicating that it has high safety.
[0107] From the above content, it can be seen that the advantage of the present invention is that other impurities in the titanium dioxide by-product ferrous sulfate can be removed in a simple step, and a basic iron phosphate precursor is obtained by manganese supplementation and simple oxidation co-precipitation, thereby obtaining a high-performance lithium manganese iron phosphate positive electrode material.
[0108] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A method for preparing a lithium manganese iron phosphate positive electrode material, comprising the following steps: S1. Prepare a solution of ferrous sulfate produced as a byproduct of titanium dioxide, adjust the pH, stir, and then add manganese salt to obtain a solution containing Mn 2+ of ferrous sulfate solution; S2, to the Mn-containing 2+ Adding an oxidant and a phosphorus source to a ferrous sulfate solution, adjusting the pH, stirring, filtering and washing to obtain manganese-doped basic iron phosphate; S3, dissolving the basic ferric phosphate, neutralizing it with acid, filtering, washing the precipitate, and drying it to obtain manganese-doped ferric phosphate hydrate; S4, aerobically calcining the ferric phosphate hydrate to obtain manganese-doped anhydrous ferric phosphate; S5, mixing the anhydrous ferric phosphate, a lithium source and a reducing sugar, ball milling, and drying to obtain a mixture; S6, calcining the mixture in the absence of oxygen to obtain the lithium manganese iron phosphate positive electrode material; In step S1, the pH is 4.5-6.5; In step S2, the pH is 7-10.
2. The preparation method according to claim 1, characterized in that: In step S1, the titanium dioxide by-product ferrous sulfate refers to ferrous sulfate heptahydrate produced as a by-product in the titanium dioxide production process; The impurities and their contents in the titanium dioxide by-product ferrous sulfate are: titanium 1000-2000 ppm, manganese 800-900 ppm, and magnesium 1800-2000 ppm.
3. The preparation method according to claim 1 or 2, characterized in that: In step S1, the stirring conditions are: temperature of 60-80°C, time of 1-5 h, and stirring speed of 250-450 rpm.
4. The preparation method according to claim 1 or 2, characterized in that: In step S1, the manganese salt is manganese sulfate and / or manganese acetate; The amount of the manganese salt is 1-80 mol% of the ferrous sulfate; The Mn-containing 2+ The molar ratio of manganese to iron in the ferrous sulfate solution is (0.67~1):
1.
5. The preparation method according to claim 1 or 2, characterized in that: In step S2, the oxidant is one or more of hydrogen peroxide, oxygen and sodium chlorate; The molar ratio of the oxidant to the ferrous sulfate is (0.45-0.55): 1; The feed rate of the oxidant is 0.1-0.5 ml / min; The phosphorus source is one or more of ammonium phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate and phosphoric acid; The molar ratio of phosphorus to iron in the basic ferric phosphate is 1:(1.01-1.05); The feeding rate of the phosphorus source is 3-5 ml / min.
6. The preparation method according to claim 1 or 2, characterized in that: In step S2, the stirring conditions are: time is 1-3 h, and the stirring speed is 350-750 rpm.
7. The preparation method according to claim 1 or 2, characterized in that: In step S3, the acid is one or more of phosphoric acid, sulfuric acid, oxalic acid and hydrochloric acid; The drying conditions are: temperature of 50-80° C. and time of 6-12 hours.
8. The preparation method according to claim 1 or 2, characterized in that: In step S4, the conditions for aerobic calcination are: temperature of 500-700° C. and time of 3-6 h.
9. The preparation method according to claim 1 or 2, characterized in that: In step S5, the lithium source is one or more of lithium carbonate, lithium hydroxide and lithium acetate; The lithium source Li + With the anhydrous iron phosphate PO4 3- The molar ratio is (1.01-1.05):1; The reducing sugar is one or more of glucose, fructose and galactose; Based on the lithium manganese iron phosphate positive electrode material, the amount of reducing sugar is 10% to 20%; The ball milling conditions are: ball milling speed 300-600 rpm / min, ball milling time 4-8 h; The drying conditions are: temperature of 50-80° C. and time of 3-6 hours.
10. The preparation method according to claim 1 or 2, characterized in that: In step S6, the conditions for oxygen-free calcination are: in an inert atmosphere, a temperature of 650-850° C., and a time of 8-12 h; The inert atmosphere is nitrogen or argon; The structural formula of the lithium manganese iron phosphate is LiMn x Fe 1-x PO4, where x is 0.40~0.50; The particle size of the lithium manganese iron phosphate is 1-15 μm.
Citation Information
Patent Citations
Lithium manganese ferric phosphate (LMFP) material with core-cell structure as well as preparation method and application thereof
CN106299296A
Lithium manganese phosphate composite material as well as preparation method and application thereof
CN109742340A
Cited By
Doped ferromanganese phosphate precursor material and preparation method thereof
CN120864465A